2015
DOI: 10.1002/pc.23401
|View full text |Cite
|
Sign up to set email alerts
|

Containment capability of 2D triaxial braided tape wound composite casing for aero‐engine

Abstract: Two-dimensional (2D) triaxial braided composites have been successfully used in aero-engine fan containment system for weight reduction. In the current study, blade containment tests were conducted on highspeed rotor spin tester to investigate the containment process and failure mechanisms of the composite casing. The composite casing was fabricated by winding 2D carbon fiber triaxial braided tape on a capstan into predetermined thickness and then infused with epoxy resin. Test results indicate that the damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…The numerical simulated damage patterns of 2DTBC are similar with those reported in [6,7], which also used a highly efficient homogenized model to simulate the impact performance of a two-dimensional triaxial braided composite casing. While the previous studies [6] were concerned with the effect of projectile shape, this study analyzed more extensively the damage morphology of composites with different architecture.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The numerical simulated damage patterns of 2DTBC are similar with those reported in [6,7], which also used a highly efficient homogenized model to simulate the impact performance of a two-dimensional triaxial braided composite casing. While the previous studies [6] were concerned with the effect of projectile shape, this study analyzed more extensively the damage morphology of composites with different architecture.…”
Section: Resultssupporting
confidence: 69%
“…Overall, it is found that when the angles α and β are larger than 20°, the damage tolerance for the composite panels is substantially unchanged against the change of projectile deflection angle α , while the impact resistance changes a lot against the change of velocity deflection angle β . Most of the existing studies deal with the effect of projectile shapes and material properties on the damage behavior of composite plates [2,3,4,5,6,7,8,9]. This study provides additional understanding on the effect of architecture type and impact attitudes on the impact resistance of composite panels, which could be useful for the design of composite protective structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hundreds of papers have been published, wherein the authors used cohesive elements in ply-level simulations of FRP impact loading [16][17][18][19][20][21][22][23][24]. This approach is quite effective and allows using both shell and solid elements in calculations.…”
Section: Meso-scale (Ply/yarn Level)mentioning
confidence: 99%